Coset decomposition method for storing and decoding fingerprint data - Sayed, Mohamed (Journal of Advanced Computer Science & Technology, 2014)
Biometrics such as fingerprints, irises, faces, voice, gait and hands are often used for access control, authentication and encryption instead of PIN and passwords. In this paper a syndrome decoding technique is proposed to provide a secure means of storing and matching various biometrics data. We apply an algebraic coding technique called coset decomposition to the model of fingerprint biometrics. The algorithm which reveals the matching between registered and probe fingerprints is modeled and implemented using MATLAB.